2012
DOI: 10.1134/s0362119712020065
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous electrical stimulation of the spinal cord: A noninvasive tool for the activation of stepping pattern generators in humans

Abstract: A new method for the activation of spinal locomotor networks (SLN) in humans by transcutane ous electrical spinal cord stimulation (tESCS) has been described. The tESCS applied in the region of the T11-T12 vertebrae with a frequency of 5-40 Hz elicited involuntary step like movements in healthy subjects with their legs suspended in a gravity neutral position. The amplitude of evoked step like movements increased with increasing tESCS frequency. The frequency of evoked step like movements did not depend on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 25 publications
1
47
0
5
Order By: Relevance
“…Одной из таких технологий является неинвазивная электрости-муляция спинного мозга [13] . В настоящее вре-мя в литературе стали появляться исследования, посвященные вопросам чрескожной спинальной электростимуляции у пациентов с ДЦП, которые указывают на эффективность и перспективность этой методики в двигательной реабилитации де-тей со спастическими параличами [14] .…”
Section: Introductionunclassified
“…Одной из таких технологий является неинвазивная электрости-муляция спинного мозга [13] . В настоящее вре-мя в литературе стали появляться исследования, посвященные вопросам чрескожной спинальной электростимуляции у пациентов с ДЦП, которые указывают на эффективность и перспективность этой методики в двигательной реабилитации де-тей со спастическими параличами [14] .…”
Section: Introductionunclassified
“…У детей наиболее перспективным является использование метода неинвазивной чрескожной электростимуляции спинного мозга (ЧЭССМ) [8].…”
Section: Introductionunclassified
“…We have shown that locomotor training combined with epidural electrical spinal cord stimulation (SCS) facilitated the recovery of voluntary leg movements in motor complete SCI patients [1,14]. Recently, we developed a method of electrically activating the spinal circuitry via electrodes placed on the skin overlying the lower thoracic vertebrae and demonstrated that in healthy subjects the involuntary locomotor-like movements can be induced by transcutaneous SCS [11,12]. The positive effect of using transcutaneous SCS (TSCS) was observed in SCI patients as well.…”
Section: Introductionmentioning
confidence: 99%